2013
DOI: 10.3892/ijmm.2013.1232
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and apoptosis in tubular cells following unilateral ureteral obstruction are associated with mitochondrial oxidative stress

Abstract: Tubular epithelial loss has been shown to be responsible for the formation of atubular glomeruli leading to nephron decomposition and interstitial fibrosis in obstructive uropathy. Cells undergoing apoptosis and autophagic cell death play an important role in this process, yet the mechanisms are not fully understood. In this study, we aimed to investigate whether autophagy cooperating with apoptosis is associated with mitochondrial damage and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 28 publications
(39 reference statements)
3
73
0
Order By: Relevance
“…Although it is uncertain whether or not this persistent autophagy can directly cause tubular cell death, recent studies have consistently demonstrated that UUO-induced autophagy in proximal tubules (14 d of duration) may act in concert with apoptosis to induce tubular atrophy and nephron loss that is associated with the progression of interstitial fibrosis. 28,29,31 In this study, when autophagy was impaired in PT-Atg7 KO mice, UUO-induced tubular atrophy and nephron loss was significantly reversed (Fig. 5E to G), further suggesting a role for persistent induction of autophagy in tubular degeneration during renal fibrosis.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Although it is uncertain whether or not this persistent autophagy can directly cause tubular cell death, recent studies have consistently demonstrated that UUO-induced autophagy in proximal tubules (14 d of duration) may act in concert with apoptosis to induce tubular atrophy and nephron loss that is associated with the progression of interstitial fibrosis. 28,29,31 In this study, when autophagy was impaired in PT-Atg7 KO mice, UUO-induced tubular atrophy and nephron loss was significantly reversed (Fig. 5E to G), further suggesting a role for persistent induction of autophagy in tubular degeneration during renal fibrosis.…”
Section: Discussionsupporting
confidence: 53%
“…[28][29][30][31][32]35 Using pharmacological and genetic inhibitory approaches, our study has determined the regulation of renal interstitial fibrosis by autophagy in the in vivo model of UUO and in vitro model of TGFB1-treated proximal tubular cells. The results show that blockade of autophagy by pharmacological inhibitors (choloroquine and 3-methyladenine) or conditional Atg7 deletion from proximal tubules suppressed renal interstitial fibrosis during UUO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations